Analysis of FM/FM/c queuing system: using fuzzy approach and parametric nonlinear programming. (2016) - Bagherinejad, Jafar; Pishkenari, S.B.
Applying fuzzy principles and approaches to the queue systems will provide more extensive and realistic applications of them. A queue system of M/M/c is studied based on fuzzy approach in this paper. This system was proposed as a FM/FM/c system with probability of the presence of customers in the system and utility factor. In addition, performance measurement was developed using the concept of parametric nonlinear programming and characteristics of fuzzy numbers. For further analysis, a FM/FM/c queuing system was considered to determine most appropriate value for the number of servers by using the concept of fuzzy relations and inference and fuzzy multiple objective decision making. The results of this research show that we can determine appropriate number of servers and we can do it perfectly and actually analyse based on system situations and management preferences.